The Role Of Early Childhood Education Teachers In Stimulating The Development Of Prosocial Behavior In Group B Children (A Qualitative Descriptive Study at Taman Ilmu Early Childhood Education in Lebong Regency) - Roma, Weni Sika; Pebriani, Ela; Mayasari, Henni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this research is to describe the role of teachers in stimulating the development of prosocial behavior in children in group B at the Taman Ilmu Early Childhood Education in Rejang Lebong Regency. The type of research used in this study is descriptive qualitative research. The data collection methods used are interviews, observations, and documentation. The data sources are teachers and the headmaster at the Taman Ilmu Early Childhood Education in Rejang Lebong Regency, and the documentation includes photos taken during interviews with the teachers and headmaster. The data reduction involves recording the results of interviews with the teachers and headmaster, coding the data according to the information provided by the informants, displaying data by detailing the results of interviews with the teachers and headmaster, and verifying the data by reconsidering interview results, reviewing field notes, rethinking observational data, and field findings, in order to draw conclusions from the research results that have been conducted. The results of this study describe the role of teachers in stimulating the development of prosocial behavior in group B children at the Taman Ilmu Early Childhood Education in Rejang Lebong Regency. Teachers provide examples or role models in giving motivation and consistent stimuli, emphasize the importance of prosocial norms, provide opportunities for positive interaction, teach responsible behavior, and foster good relationships with students.